PERAN MASYARAKAT DALAM MENDUKUNG PEMBANGUNAN DI INDONESIA - Asep Hidayat (JISOS: JURNAL ILMU SOSIAL, 2024)
Community participation in the development planning process is very important because it can foster an attitude of belonging and a sense of community responsibility towards development planning. Society as one of the state subsystems must involve themselves in the development process. The involvement starts from the development planning stage, implementation, to the supervision stage. Without community involvement, the results of development will not necessarily answer the needs of the community and the welfare of the community has not been achieved. The purpose of this study was to determine community participation in development in Indonesia. In every development planning, it is necessary to have a contribution in the form of thoughts, ideas, criticisms and suggestions voluntarily from the community for a development. so that in every decision making there is a socialization of the community must also be involved in every decision making. In principle, community participation in infrastructure development is very influential on the course of the infrastructure development process of the Indonesian state, the implementation of development is not solely the responsibility of the government or the apparatus, but also the shared responsibility of the entire community